Combined Microscopic and Endoscopic Surgery for Pineal Region Meningiomas Using the Occipital-Parietal Transtentorial Approach - Ding, Yu; Sun, Liang; Hu, Yukun; Zhai, Weiwei; Zhang, Liexiang; Yu, Zhengquan; Wu, Jiang; Chen, Gang (Frontiers in Oncology, 2022)
Objective: Pineal region meningiomas are deeply located and adjacent to critical neurovascular structures, making them one of the most challenging areas to access. The authors presented a combined microscopic and endoscopic surgery and investigated its value in resecting pineal region meningiomas. Methods: Twelve patients with pineal region meningiomas from February 2017 to December 2020 were retrospectively reviewed. All patients underwent combined microscopic and endoscopic surgery using the occipital-parietal transtentorial approach. Perioperative clinical, surgical, and radiographic data were collected. Results: The endoscope provided a wider view and increased visualization of residual tumors. All tumors were completely resected, and none of the patients died. Total resection was believed to have been achieved in four patients, but the residual tumor was detected after endoscopic exploration and was completely resected with an endoscope. Only one patient had transient visual field deficits. No recurrence was observed during follow-up. Conclusions: Combined microscopic-endoscopic surgery for pineal region meningiomas eliminates microscopic blind spots, thus compensating for the shortcomings of the traditional occipital transtentorial approach. It is a promising technique for minimally invasive maximal resection of pineal region meningiomas.